The Observatory for the Knowledge Librarianship (OCOBI): Achievements and Challenges of Research in Librarianship School of Library and Information Science - Sandí Sandí, Magda Cecilia (2011)
This article showing the intensive work in the School of Library and Information Science about the research. Include an important description with the principals actions starting with the School for pushing the research. This article shows the most relevant challenges in the next five years. In fact, the research in the library science field in Costa Rica is engaged and linked with the creation and education for the librarian profession. The most among the papers in the Library and Information Science are result the researchers by students for the obtain their superior grade "Licenciatura" more than the bachelor. Also, there are papers in the other level, for example the Master Degree produces many researches in the Information Management. Finally, is evident the contribution of the teachers-researchers in the Library and Information Science School, it reflect in articles, papers and researchs about the Library Science y other issues. These documents are very important for us, because are using for the learning, social extension and research, too.